Spatial Adaptation of Railway Stations: Arrival of High-Speed Rail Network - Juan Bautista Font Torres; Jorge Luis García Valldecabres; Luís Cortés Meseguer (Infrastructures)
In the years since the emergence of the railway, the main objective has been focused on trains arriving and stopping at stations, with stations being considered a secondary or even residual objective for bringing people or goods on or off. The arrival of high-speed trains at stations has allowed for the creation of integrated, environmentally friendly stations which have become mobility hubs, connecting different modes of transportation and cities, as well as being clusters of economic activities that stimulate the inclusive growth of the areas where they are located. These transport infrastructures condition the social and communication relationships of many spaces. The consequences that have been demonstrated in the stations analyzed have been strengthened intermodally with other means of transport, giving value to commercial developments and old stations, as well as the environments where they are located, a development aimed beyond the railway users themselves. From an operational point of view, the main consequence of this transformation is the necessity to absorb the increase in passenger demand. The integration of the railway within an urban space is shaped through the construction of new stations within the already existing urban framework or, in some cases, by relocating them to the periphery of the city. New stations have undergone changes compared to those built a century ago. Their conception has evolved, adapting to the architecture of their time, but the most radical change they have experienced is related to the new uses that have been developed within them and how these spaces are utilized. The introduction of high-speed trains has initiated a series of reflections on new station concepts. The new operation is characterized by journey times, frequency, and comfort. This comfort is not only perceived on board a train but also in stations during a passenger’s stay, which has a direct impact on the design of stations. Provisional railway stations are valuable tools in situations where flexibility, speed, and reduced costs are required. Although they are not designed to be permanent, their ability to adapt to specific needs makes them a strategic option for temporary projects, though not in the case studied of the Valencia station. The planning of projects makes it necessary to implement proxemic standards in the design of spaces that contribute to the diversification of economic activity around and in a station itself, such as commercial, residential, or cultural areas.